Peningkatan Kompetensi Mengembangkan RPP melalui Lesson Study bagi Guru SD Laboratorium - Achmad Supriyanto; Wasih DS; Roni Herdianto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstrack: This School Action Research aims to uncover and describe teacher competencies in developing Lesson Plans, and implementing lesson studies. This SAR was designed with the Mc Taggart's classroom action research design in two action cycles. The research subjects were 11 elementary school teachers. The research instrument was developed by researchers in the form of work tables 1—5 to collect teacher competency data designing 10 components of lesson plans, and field notes to record the implementation of lesson study. The data collected was reduced to two main data, analyzed qualitatively and quantitatively using the mean and percentage techniques. The results of SAR cycle 1 showed that the competence to design the components of the lesson plan with a C value was 50%, a competence with a B value was, and the rest of 10% need further guidance. The results of SAR cycle 2 showed that 100% of teacher could achieve B value in designing lesson plans. Thus, it is proven that lesson study can improve teacher competence in developing lesson plans. Abstrak: Penelitian Tindakan Sekolah ini bertujuan mengungkap dan mendeskripsikan kompetensi guru mengembangkan Rencana Pelaksanaan Pembelajaran dan pelaksanaan lesson study. Penelitian Tindakan Sekolah ini dirancang dengan rancangan penelitian tindakan kelas model Mc.Taggart dalam dua siklus tindakan. Subjek penelitian 11 orang guru SD. Instrumen penelitian dikembangkan oleh peneliti berupa tabel kerja 1—5, untuk menghimpun data kompetensi guru merancang 10 komponen RPP, dan catatan lapangan untuk mencatat pelaksanaan lesson study. Data yang terkumpul direduksi menjadi dua data utama, dianalisis secara kualitatif dan kuantitatif dengan teknik rerata dan persentase. Hasil PTS siklus I menunjukkan 50% kompetensi merancang komponen RPP dengan nilai C, 40 % nilai B, 10% nilai dengan predikat perlu bimbingan. Hasil Penelitian Tindakan Sekolah siklus II 100% kompetensi merancang komponen RPP dengan nilai B. Jadi, terbukti lesson study dapat meningkatkan kompetensi guru mengembangkan RPP.